SPAWNING BEHAVIOUR AND FECUNDITY OF THE INDIAN MACKEREL, RASTRELLIGER KANAGURTA (CUVIER), AT MANGALORE - Rao, V Ramamohana (Indian Journal of Fisheries, 2011)
The earliest reference to the fecundity of the Indian mackerel was by Devanesanand John (1940) who estimated the number of ripe eggs in the mackerel ovary as94,000. Subsequent work was directed mostly towards finding out the spawningbehaviour of this fish, by the study of the intra-ovarian eggs. Pradhan (1956)indicated the possibility of the Indian mackerel spawning the eggs in successive batchesover a prolonged period, like its Atlantic counter-part Scomber scombrus (L). Pradhanand Palekar (1956) described the maturity stages I to VII, based on the externalappearance of the ovary, its size relative to the abdominal cavity, and the range ofova-diameter readings. However, they have not given any ova-diameter frequencypolygons. Sekharan (1958) studied the ova-diameter frequency in a few ovaries ofthe mackerel, ranging in maturity stage from II-III to V-VI, VI-VII and a few spentovaries. He stated that his investigation showed a possibility of the mackerel eggsripening in batches and of their release in succession. Radhakrishnan (1962),adopting the method followed by Clark (1934), Prabhu (1956), and Qasim and Qayyam(1961), studied the ova-diameter frequency seasonally and indicated the possibilityof the mackerel shedding its eggs in batches. Vijayaraghavan (1962) followed adifferent procedure. Employing very high magnification, he measured ova withdiameter greater than 0.525 mm. Plotting this frequency with a small size interval(3.5^) he claims the modes were clearly distinguishable. These modes according tohim were well-defined batches of eggs ripening in succession. Rao (1962) studiedthe ova-diameter frequency in maturity stages I-V and VII. However, spawn-ripeovary corresponding to stage VI, as he stated, was not obtained in his study.